okay these divisibility inductions are always a little dicey, but here goes:
(btw i assumed it to be 2n3 - 2n)
Show true for n=1:
2(1) - 2(1)
= 0
= 12(A) (where A = 0)
Therefore true for n=1
Assume true for n=k:
2k3 - 2k = 12B (where B is any integer)
Show true for n=k+1:
2(k+1)3 - 2(k+1)
= 2k3 + 6k2 + 4k
= (2k3 - 2k) + 6k2 + 6k
= 12B + 6k(k+1) (from assumption, where B is any integer)
With 6k(k+1), either k or k+1 is even, so k(k+1) will be divisible by 2
So (2k3 - 2k) + 6k(k+1)
= 12B + 6(2)C (where C is any integer)
= 12(B+C)
Therefore divisible by 12
Therefore true for n=k+1, so by induction true for all n>=1.
Hope this helps!